Mast cell amines and inosineinduced vasoconstriction in the rat hind limb - A. M. Northover; B. J. Northover (Mediators of Inflammation, 1997)
Under certain circumstances injected inosine causes a net vasoconstrictive effect on the arterioles, which has been attributed to 5-hydroxytryptamine (5HT) released in response to adenosine type 3 (A3) receptor stimulation of mast cells residing in the adventitia. We have sought further evidence for this hypothesis using blood vessels of the rat hind limb perfused in vitro at constant rate with a gelatin-containing physiological salt solution. Injection of inosine (2.7 mg) caused a rise in perfusion pressure, which was only slightly increased by inclusion of N-nitro-L-arginine methyl ester (100 μM) in the perfusate. Inclusion in the perfusate of cyproheptadine (1 μM), compound 48 80 (1 μg ml), 8-phenyltheophylline (1 μM) or 8-cyclopentyl-1,3 dipropylxanthine (0.1 μM) greatly reduced the pressor response to inosine. The pressor effect of injected 5HT (400 μg) was abolished by pre-treatment with cyproheptadine, but not by pre-treatment with compound 48 80. These results suggest that the net pressor response to injected inosine was mainly the result of an A1 receptor-mediated release of 5HT, most probably from mast cells. No evidence was found for an involvement of A3 receptor stimulation.